Pengaruh Financial Technology Dalam Meningkatkan Literasi Keuangan Usaha Mikro Kecil dan Menengah Kota Palembang - Mustikasari, Yayuk; Noviardy, Andrian (Direktorat Riset dan Pengabdian Kepada Masyarakat Universitas Bina Darma, 2020)
This study aims to analyze the role of fintech in improving the financial literacy of UMKM in Palembang City. In this study, researchers used 42 randomly selected responses, namely UMKM actors in Seberang Ulu 1 and 2 Districts, Palembang city. This study uses data collection techniques using primary and secondary data. The aim is to determine the effect of fintech and literacy variables on UMKM in Palembang City. The hypothesis testing method used in this study is the t-test. Based on the test results using the t-test that the financial technology variable in improving UMKM financial literacy in Palembang City has a T value or P-value <0.05, identifying a positive relationship between the dependent variable (Y) and the independent variable (X). This means that there is a significant influence between the two variables.